A Review of Necrotauliids from the Triassic/Jurassic of England (Trichoptera: Necrotauliidae) - Richard S. Kelly; Andrew J. Ross; Robert A. Coram (Psyche: A Journal of Entomology)
Species previously attributed to Necrotauliidae are revised from the Late Triassic and Early Jurassic of England based on examination of type specimens and non-type material. The necrotauliids have been considered as a basal family of caddisflies (Trichoptera) or as a paraphyletic assemblage of stem-amphiesmenopterans. Herein a new genus, Austaulius, is erected which includes all Lilstock Formation∖Lower Lias material from England; the previously described species are synonymized with A. furcatus and a new species, A. haustrum, is described from the Dorset Coast, the holotype of which preserves synapomorphic traits of the Trichoptera not previously described suggesting that the family is trichopteran. The type genus remains Necrotaulius and type species N. parvulus (Geinitz, 1884) from the type locality of Dobbertin, Germany. One species of Necrotaulius is represented in the UK, N. parvulus, which is found in the Upper Lias.